Design and analysis of spatial encoding circuits for peak power reduction in on-chip buses. - Kaul, H. (IEEE Transactions on VLSI systems)
We propose various low-latency spatial encoder circuits based on bus-invert coding for reducing peak energy and current in on-chip buses with minimum penalty on total latency. The encoders are implemented in dual-rail domino logic with interfaces for static inputs and static buses. A spatial and temporally encoded dynamic bus technique is also proposed for higher performance targets. Comparisons to standard on-chip buses of various lengths with optimal repeater configurations at the 130-nm node show the energy-delay and peak current-delay design space in which the different encoder circuits are beneficial. A 9-mm spatially encoded static bus exhibits peak energy gains beyond that achievable through repeater optimization for a single-cycle operation at 1 GHz, with delay and energy overhead of the encoding included. For throughput-constrained buses, the spatially encoded static bus can provide up to 31% reduction in peak energy, while the spatially and temporally encoded dynamic bus yields peak current reductions of more than 50% for all bus lengths. The encoder circuits show good scaling properties since the performance penalty from encoding decreases with scaled interconnects.